Haemophilia A and B as a cause for secondary osteoporosis and increased fracture risk. Issue 6 (September 2015) - Anagnostis, Panagiotis; Karras, Spyridon; Paschou, Stavroula A.; Goulis, Dimitrios G.
<x xml:space="preserve">Abstract</x> Despite the increasing evidence regarding its association with low bone mineral density (BMD) both in adults and children, haemophilia A or B has not yet been considered among the classic causes of secondary osteoporosis. Although the exact mechanisms are not fully elucidated, physical inactivity and vitamin D deficiency seem to play a fundamental role for such an association. Viral infections and arthropathy further compromise bone mass. Except for low BMD, patients with haemophilia seem to be at increased risk for fracture and falls. The FRAX tool may be of value in this population, for the estimation of fracture risk. Regular exercise, prophylactic factor replacement therapy in severe haemophilia, fall prevention strategies and optimization of calcium and vitamin D intake are recommended. In any case, individualized multidisciplinary approach and careful assessment and management of fracture risk are recommended.